The influence factors of social media users on intention to adopt a zero-waste lifestyle in Petaling, Selangor. / Siti Aishah Mohd Shafie, Aniz Nazirah Borhan and Nur Balqis Basyirah Abdullah - Mohd Shafie, Siti Aishah; Borhan, Aniz Nazirah; Abdullah, Nur Balqis Basyirah (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Zero-waste should be practiced in managing waste disposal or production, preventing pollution, conserving natural resources, improving quality of life and well-being. Encouraging a sustainable practice in social media is one of the solutions to raise awareness of a zero-waste lifestyle. In Malaysia, Selangor has been identified as the highest waste producing state, and within the state, the highest populated district is the Petaling district. As a result, the Petaling district is where this study is being explored. In addition, this study emphasizes gender, age group, peers’ impressions of zero-waste posts on social media, and the ability to distribute zero-waste information on social media. This study aims to investigate the factors that influence social media users’ intentions to adopt a zero-waste lifestyle in Petaling. In this study, 210 observations were chosen as samples. The method that is being used in this study is logistic regression analysis. Overall, based on the results, it appears that peers’ impressions of zero-waste posts on social media serve as a significant influencing element.